Pharmacokinetics, Pharmacodynamics, and Safety of Dulaglutide After Single or Multiple Doses in Chinese Healthy Subjects and Patients with T2DM: A Randomized, Placebo-Controlled, Phase I Study - Xu, Junyu; Zhang, Yifei; Li, Yiming; Zhao, Xia; Zhou, Weiwei; Loghin, Corina; Tham, Lai San; Cui, Xuewei; Cui, Yimin; Wang, Weiqing (Advances in therapy, 2022)
Introduction This study evaluated the pharmacokinetics, pharmacodynamics, and safety of a single dulaglutide dose in Chinese healthy subjects and of multiple dulaglutide doses in Chinese patients with type 2 diabetes mellitus (T2DM). Methods This two-part, double-blind, placebo-controlled study included 16 healthy subjects randomized to receive a single dose of placebo and two of three dulaglutide doses (0.5 mg, 0.75 mg, or 1.5 mg) in three treatment periods, and 42 patients with T2DM randomized to receive placebo or one of the three dulaglutide doses once weekly for 4 weeks. Pharmacokinetics and safety parameters were assessed in all participants, and pharmacodynamics effects were investigated in patients with T2DM. Results Following a single-dose administration of 0.5 mg, 0.75 mg, or 1.5 mg dulaglutide in healthy subjects, geometric mean maximum concentrations ( C max ) were 29.4, 44.2, and 81.5 ng/mL, respectively. Following weekly administration in patients with T2DM for 4 weeks, C max were 26.3, 41.4, and 70.2 ng/mL, respectively, with accumulation ratios of 1.33–1.39. Geometric mean for half-life of 4–5 days and median time to C max ( t max ) of approximately 48 h were observed in both study populations. Dose-proportional increases in drug exposure were observed after both single and multiple dosing. Significant reductions in baseline-corrected fasting glucose and hemoglobin A1c (HbA1c) were observed in patients with T2DM who received dulaglutide 0.75 mg and 1.5 mg. Dulaglutide was well tolerated, with the majority of adverse events being gastrointestinal disorders of mild severity. Conclusions Pharmacokinetics, pharmacodynamics, and safety profiles of dulaglutide demonstrated in the present study support a once-weekly dosing regimen in Chinese patients with T2DM. Trial Registration NCT01667900 (ClinicalTrials.gov).